Hipotesis pergerakan dan enklitik -nya: implikasi terhadap teori kasus dan teoriteta (Jurnal Bahasa, 2007)
This article discusses in detail the application of Movement Hypothesis which had explained the cliticization of enclitic "-nya" (Jurnal Bahasa, June 2006) in Malay language. The analysis can be strengthened the case and theta theory which had implication due to the movement hypothesis can be explained in detail. The implication towards the case and theta theory was discussed b; Aoun (1982), Kayne (1975) and Jaegg!i (1982). These three experts had a different view towards the theta mark and case assignment. They named the theta marking and case assignment to the certain clitics as theta absorption and case absorption. Therefore, this writing will concentrate on the theta mark at the D-structure and case assignment at the L-structure and explain the theta and case absorption by the enclitic "-nya" in Malay language.